A game-based learning approach to sleep hygiene education: a pilot investigation - Seaver, Christine; Bowers, Clint; Beidel, Deborah; Holt, Lisa; Ramakrishnan, Sridhar (Frontiers in Digital Health, 2024)
Introduction Sleep hygiene education (SHE) consists of environmental and behavioral practices primarily intended to reduce sleep problems. Currently considered ineffective as a stand-alone treatment, the manner in which the education is typically delivered may be ineffective for the acquisition of new knowledge. The purpose of this study was to determine if a more engaging teaching medium may improve the efficacy of sleep hygiene education. This study examined the use of game-based learning to teach SHE to individuals with sleep problems. Methods 35 participants played the SHE games for 30 days. Differences in pre- and post-state anxiety and sleep quality measures were examined. Results Participants had significant improvements in sleep quality and state anxiety after using the app for 30 days, although scores for the majority of patients remained elevated. Discussion This pilot investigation provides initial evidence for the efficacy of a game-based approach to SHE.